Kajian Sedimentasi pada DAS Sail Pekanbaru dengan Menggunakan SIG dan Metode USLE - Aisah kurnia utami; Manyuk Fauzi; Bambang Sujatmoko (JURNAL TEKNIK, 2019)
Modifying of Sail watershed land-use will increase the surface flow and causes erosion and sedimentation. USLE is used for estimating the soil erosion and GIS is used for predicting the size of USLE parameters. The results of the analysis show that erosion occurred at DAS Sail is a category of low class (15-60 ton/ha/year). The results of the research show that on some sub DAS Sail there is land sediment because the erosion value is greater than the value of the carrying capacity, such as sub DAS 1 with the value 11833130.27 > 25924.71115 (SE > Tc) and Sub DAS 2 with a value of 61212.60687 < 800875.7768 (SE < Tc) does not occur because the erosion value shows less than the value of carrying capacity occurring in the watershed